1979
DOI: 10.1056/nejm197911013011803
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Antiplatelet and Anticoagulant Therapy to Improve Patency of Grafts after Coronary-Artery Bypass

Abstract: Fifty patients who underwent aortocoronary saphenous-vein bypass-graft surgery were randomly assigned to one of three groups to determine the effects of antiplatelet or anticoagulant therapy on graft patency. Twenty-four patients served as controls; 13 patients received aspirin (325 mg three times a day) and dipyridamole (75 mg three times a day); and 13 patients received closely regulated warfarin therapy. Medications were begun on the third post-operative day. Six months after surgery, all patients underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(35 citation statements)
references
References 39 publications
0
33
0
2
Order By: Relevance
“…Recent studies showed that platelets play a significant role in the pathogenesis of VTE and antiplatelet agents can have a protective effect against the first episode of VTE in patients with hip fracture or undergoing hip arthroplasty (n=13 356) and recurrent VTE after treatment with systemic anticoagulation 87, 88, 89, 90, 91. Our results showed that aspirin appears to be effective in reducing VTE after cardiac surgery in the pediatric population (using 5 mg/kg/day)45 or when a higher dose of aspirin is used in adults (>300 mg/day) 68. Evidence suggests that aspirin resistance is common within the first week after cardiac surgery and the standard low‐dose aspirin (100 mg/day) would not be adequate to exert its full antiplatelet effects in many patients 11, 12, 13.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recent studies showed that platelets play a significant role in the pathogenesis of VTE and antiplatelet agents can have a protective effect against the first episode of VTE in patients with hip fracture or undergoing hip arthroplasty (n=13 356) and recurrent VTE after treatment with systemic anticoagulation 87, 88, 89, 90, 91. Our results showed that aspirin appears to be effective in reducing VTE after cardiac surgery in the pediatric population (using 5 mg/kg/day)45 or when a higher dose of aspirin is used in adults (>300 mg/day) 68. Evidence suggests that aspirin resistance is common within the first week after cardiac surgery and the standard low‐dose aspirin (100 mg/day) would not be adequate to exert its full antiplatelet effects in many patients 11, 12, 13.…”
Section: Discussionmentioning
confidence: 67%
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
“…The ongoing Clopidogrel After Surgery for Coronary Artery Disease (CASCADE) trial will assess the addition of clopidogrel to aspirin using angiography and intravascular ultrasound one year after the operation (24). Several trials have investigated the use of vitamin K antagonist (VKA) anticoagulants (25)(26)(27). Only one study (26), in which oral VKA started after postoperative day 7 was compared with no anticoagulation, showed some improvement from the control group.…”
Section: Prevention Antiplatelet Therapymentioning
confidence: 99%
“…However, no benefit was seen in terms of graft patency in these early studies because of limited trial enrollment and late administration, typically ≥3 days after surgery. [11][12][13] In one of the first studies assessing aspirin administration within the early hours after surgery, Chesebro et al 14 conducted a controlled trial comparing graft patency in 407 patients randomized to placebo or the combination of aspirin and dipyridamole beginning as early as 7 hours after surgery. Within 1 month of surgery, vein graft patency was significantly higher in patients treated with antiplatelet therapy (98% versus 90%, aspirin and dipyridamole versus placebo; P<0.0001).…”
mentioning
confidence: 99%